(untitled) (European Journal of Marketing and Economics, 2023)
In a globalized and interdependent world, every country needs cooperation and partnership. In the framework of this mission, every state undertakes policies and reforms that impose radical internal changes. Supporting these changes requires financial and human resources that states are trying to secure through various sources. Diaspora is in fact the first catalyst that provides incentives to the economy to meet national needs with financial and human resources and that helps overcome relative isolation from global trade flows. Through the engagement of the diaspora, states are extending their political and administrative functions beyond national borders and through agreements are improving relationships with other countries. This stimulates the interest of foreign investors who are always looking for new markets, less expensive, rich in natural sources. FDI through financial capital and foreign currency it brings, technological innovation, human capital development, trade opening contributes to the economic growth of the country. In other words, the state with the power given by law can create a bridge of communication between these two fundamentally different phenomena. So, the purpose of this paper is to investigate the relationship between the institutions created to support the diaspora, with the level of FDI flows. Then we go beyond this analysis to study if the type of institution engaged in this issue matters. We use data collected through different public data sources and panel econometric models are estimated for a sample of 20 countries over a 30-year period (1990-2020). Panel data analysis was conducted, implementing three different models (Pooled Model, Fixed Effect, Random Effect) Our results initially show that diaspora institution is a variable positively correlated with the volume of FDI and statistically significant. Second, based on the results, we conclude that, regardless of the type of institution engaged in the issue of diaspora, there is a statistically significant positive effect on the attraction of FDI.